PERBEDAAN PERKEMBANGAN ANAK USIA TODDLER (1-3 TAHUN) ANTARA IBU BEKERJA DAN TIDAK BEKERJA DI WILAYAH KERJA POSYANDU PUSKESMAS KAWANGKOAN (JURNAL KEPERAWATAN, 2018)
Abstract:Child development is the result of maturation of organs, especially the central nervous system. In the development there are steps that must be passed by the child to get to adulthood. The most important stage is in the first 3 years, because at this time grows rapidly developing and determining the future of children someday. (IDAI, 2009). Objective: to know difference of toddler age children (1-3 years) between working mother and not working in posyandu work area of Kawangkoan Health Center. Sample: taken by total sampling technique, that is 30 people. Research Design: Compositional analytic and sampling technique 30 people using observation sheet. Results: Wilcoxon test was obtained with significant values (0.04 or